Facial Asymmetry: Brow and Ear Position - Perumal, Balaji; Meyer, Dale R. (Facial Plastic Surgery, 2018)
The purpose of the current study was to analyze brow and ear position, and examine the relationship between these structures in patients presenting for blepharoplasty evaluation. A retrospective chart review was performed, which included all patients presenting to one oculoplastic physician for a blepharoplasty evaluation from November, 2012 to March, 2014. The prevalence of brow ptosis and brow and ear asymmetry was calculated; the proportional distribution was determined, and chi-square analysis and the z-test of proportions were used to calculate the significance. Institutional Review Board approval was obtained for this study. A total of 133 patients met the inclusion criteria. Some degree of brow ptosis was noted in 83% of patients. Brow asymmetry was found in 88% of patients, and ear asymmetry in 77%. Of those patients who had asymmetry, 61% had the right brow lower and 75% had the right ear lower; 73% of all patients had the brow and ear lower on the same side (p < 0.001). In this study, brow ptosis and asymmetry were quite common. In addition, the side of the lower brow correlated strongly with the side of the lower ear, and the right side structures were lower more often than the left. Patients presenting for blepharoplasty evaluation may have an element of generalized facial asymmetry which includes the brows and ears. These observations can be important for preoperative planning and patient counseling.
Keywords: facial asymmetry; brow ptosis; blepharoplasty; brow asymmetry